دور المحكمة الدستورية في تجسيد مبدأ الفصل بين السلطات - صلاح الدين مسطور; محمد لمين رحماني (My University, 2023)
Summary : The role of the Constitutional Court lies in embodying the principle of separation of powers through exercising its new powers granted by the constitutional amendment of 2020. These powers include the interpretive jurisdiction, which is subject to several constraints, the most prominent of which is the existence of ambiguity in constitutional texts or lack of conformity between legislation and the constitution. In addition, the Court has the jurisdiction to settle disputes arising between the constitutional authorities, which is a guarantee to establish the principle of separation of powers by defining the Court's role in regulating the functioning of constitutional institutions and determining the jurisdictions of the constitutional authorities among themselves, as well as identifying the authorities authorized to notify the Constitutional Court in case of a dispute between these authorities. ............................. ملخص: يكمن دور المحكمة الدستورية في تجسيد مبدأ الفصل بين السلطات من خلال ممارسة اختصاصاتها الجديدة التي منحها أياها المؤسس الدستوري في التعديل الدستوري 2020 وهي الاختصاص التفسيري الذي يخضع لعدة ضوابط لعل أبرزها وجود غموض في النصوص الدستورية أو عدم وجود تطابق بين التشريعات والدستور، بالإضافة إلى اختصاص فض الخلافات الناشئة بين السلطات الدستورية والذي يعد ضمانة لإرساء مبدأ الفصل بين السلطات بتحديده نشاط المحكمة الدستورية في ضبط سير المؤسسات الدستورية وضبط اختصاصات السلطات الدستورية فيما بينها وكذا تحديد الجهات المخولة بإخطار المحكمة الدستورية في حالة حدوث خلاف بين هذه السلطات. ............................. Résumé : Le rôle de la Cour constitutionnelle réside dans la concrétisation du principe de séparation des pouvoirs en exerçant ses nouveaux pouvoirs qui lui ont été accordés par le fondateur constitutionnel dans la réforme constitutionnelle de 2020. Ces pouvoirs comprennent le pouvoir interprétatif, qui est soumis à plusieurs contraintes, dont la présence de flou dans les textes constitutionnels ou l'absence de concordance entre les législations et la Constitution. En plus de cela, la Cour constitutionnelle a le pouvoir de résoudre les litiges entre les pouvoirs constitutionnels, ce qui garantit l'établissement du principe de séparation des pouvoirs en définissant l'activité de la Cour constitutionnelle dans la régulation des institutions constitutionnelles, la régulation des pouvoirs constitutionnels entre eux, ainsi que la désignation des entités autorisées à notifier la Cour constitutionnelle en cas de litige entre ces pouvoirs.